The Pathogenesis of Syringomyelia: A Re-Evaluation of the Elastic-Jump Hypothesis - Elliott, Novak; Lockerby, D.; Brodbelt, A. (ASME International, 2009)
Syringomyelia is a disease in which fluid-filled cavities, called syrinxes, form in the spinal cord causing progressive loss of sensory and motor functions. Invasive monitoring of pressure waves in the spinal subarachnoid space implicates a hydrodynamic origin. Poor treatment outcomes have led to myriad hypotheses for its pathogenesis, which unfortunately are often based on small numbers of patients due to the relative rarity of the disease. However, only recently have models begun to appear based on the principles of mechanics. One such model is the mathematically rigorous work of Carpenter and colleagues (2003, “Pressure Wave Propagation in Fluid-Filled Co-Axial Elastic Tubes Part 1: Basic Theory,” ASME J. Biomech. Eng., 125(6), pp. 852–856; 2003, “Pressure Wave Propagation in Fluid-Filled Co-Axial Elastic Tubes Part 2: Mechanisms for the Pathogenesis of Syringomyelia,” ASME J. Biomech. Eng., 125(6), pp. 857–863). They suggested that a pressure wave due to a cough or sneeze could form a shocklike elastic jump, which when incident at a stenosis, such as a hindbrain tonsil, would generate a transient region of high pressure within the spinal cord and lead to fluid accumulation. The salient physiological parameters of this model were reviewed from the literature and the assumptions and predictions re-evaluated from a mechanical standpoint. It was found that, while the spinal geometry does allow for elastic jumps to occur, their effects are likely to be weak and subsumed by the small amount of viscous damping present in the subarachnoid space. Furthermore, the polarity of the pressure differential set up by cough-type impulses opposes the tenets of the elastic-jump hypothesis. The analysis presented here does not support the elastic-jump hypothesis or any theory reliant on cough-based pressure impulses as a mechanism for the pathogenesis of syringomyelia.